Love between Equals - Wilson, John. author. aut Link
X, 196 p.
Keywords: This book is a philosophical study of love between equals, intended for the general reader. The Introduction explains the importance of analytic philosophy. Subsequent chapters deal with (1) love as desire or need, (2) love as intrinsic friendship, (3) the politics of love, (4) altruism and paranoia, (5) justice and communication, (6) sex, and (7) the value in loving an equal, together with some remarks on the human condition in general and the importance of reason in dealing with it. A brief list of further reading is appended.